The Epstein-Barr Virus (EBV) DNA Test as a Predictor of The Course of Nasopharyngeal Cancer - Maharani, Putri; Kodrat, Henry (Indonesian Journal of Cancer, 2024)
Background: Nasopharyngeal cancer (NPC) incidence has been largely found in Southern China and Southeast Asia and was associated with Epstein-Barr Virus (EBV). Some advanced-stage NPC may still rise to local recurrence or distant metastasis and higher plasma EBV DNA was still found in locally advanced nasopharyngeal cancer (LA-NPC) at 1 month or even 3 years after completing radiotherapy (RT). Even though EBV DNA has not been widely used in clinical practice, it could be an important value for determining treatment outcomes and risk of disease relapse.Methods: This review article gathered studies from the PubMed database from 2021 to 2022. Using various searching terms 434 articles were found and were narrowed down to 7 according to the inclusion criteria. The individual review was made for each article and endpoints such as overall survival (OS), progression-free survival (PFS), distant metastasis-free survival (DMFS), disease-free survival (DFS), and local recurrence-free survival (LRFS) were drawn.Results: Overall subjects for these studies ranged up to 2,354 LA-NPC patients (median of 1,073   subjects). All studies observed the pre-treatment and post-treatment EBV DNA and only two studies observed post-neoadjuvant chemotherapy (post-NAc). EBV DNA currently is the most reliable biomarker available for clinical purposes and its versatility can be useful, especially to value prognosis and to determine the course of treatment.Conclusions: Apart from survival outcomes, pre-treatment EBV DNA is considered good for predicting the overall prognosis. Meanwhile, post-induction chemotherapy (post-IC) or post-NAc EBV DNA is suitable for adjuvant therapy indicators, especially in LA-NPC. Even though the cut-off value for the tests was still varied across laboratories (ranging from 1,500 to 4,000), post-NAc and post-treatment might have some benefit to help predict any locoregional recurrence and distant metastasis, considering pre-treatment will not change the therapeutic course completely.